Level of Trihalmothanes (THMs) in the Klang Valley`s drinking water: A preliminary survey - Khairulmaini Osman Salleh, Department of Geography, University Malaya (Lee Ming Press Company, 2014)
The interior region of Sabah derives much of its water resource from the Pegalan-Padas River system. A survey of the water quality of the Pegalan-Padas River and two of its tributaries was performed in 1992. The study involved analysis of physical water quality parameters, nutrients, insecticides, heavy metals and coliform bacteria. The results showed that heavy metals (Cd, Cu, Fe, Mn, Pb, Zn)of the river water was far below the permitted levels for drinking water. However, the unfiltered river water was contaminated by low level of organochlorine insecticides especially DDT (maximum total DDT : 0.23 ug/L). Certain streches of the river were also affected by high level of suspended solids (average 35.0 - 53.6 mg/L). Based on river classification procedures of the Department of Environment, most parts of this river system fall under Class II, indicating water quality which is suitable as a source of drinking water.